Student Characteristics in Culinary Vocational Schools for Contextual and Entrepreneurship-Based Science Learning - Asrorul Azizi; A. Wahab Jufri; Muhammad Sarjan; Yunita Arian Sani Anwar (Journal of Educational Studies, 2026)
This study aims to analyze the characteristics of students of a State Vocational High School (SMK) culinary program on Lombok Island as a basis for developing contextual and entrepreneurial-oriented science learning in the subject of "natural and social science projects" (IPAS). This study used a quantitative descriptive design involving students selected through purposive sampling from 5 schools. Data were collected using a structured questionnaire consisting of 30 items covering five dimensions: cognitive characteristics and previous learning experiences, readiness for project-based learning (PjBL), initial science process skills, entrepreneurial interest and orientation, and motivation towards contextual learning. Data were analyzed using descriptive statistics, including mean scores and categorical classifications. The results showed that students showed high readiness for project-based learning (M = 4.00), high motivation towards contextual learning (M = 3.98), and strong entrepreneurial orientation (M = 3.96). However, their cognitive characteristics (M = 3.20) and science process skills (M = 3.20) were at a moderate level. These findings reveal a gap between students' affective readiness and their cognitive-scientific competencies. This study concludes that an integrated learning approach combining project-based learning, science process skills, contextual learning, and entrepreneurship is necessary to enhance conceptual understanding and practical competency. These findings provide empirical support for the development of a contextual-based science learning model and entrepreneurship education in vocational education.